2009
DOI: 10.1590/s0037-86822009000600004
|View full text |Cite
|
Sign up to set email alerts
|

Ocular lesions in HTLV-1 infected patients from Salvador, State of Bahia: the city with the highest prevalence of this infection in Brazil

Abstract: Lesões oculares em pacientes infectados pelo HTLV-1 em Salvador, Estado da Bahia�� a cidade com maior prevalência desta infecção no Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
4
20
2
1
Order By: Relevance
“…Although the prevalence of SS in HTLV‐I‐seropositive patients was 1.55% in the present study, that is, three times as high as that found in patients presenting with symptoms typically associated with SS, it was much lower than that found in studies conducted in Japan . Differences in the prevalence of HTLV‐I‐associated diseases across countries have previously been reported; for example, the reported prevalence of uveitis is much lower in Brazil than in Japan and Martinique . Geographic location can therefore play a role in the development of certain manifestations.…”
Section: Discussioncontrasting
confidence: 83%
“…Although the prevalence of SS in HTLV‐I‐seropositive patients was 1.55% in the present study, that is, three times as high as that found in patients presenting with symptoms typically associated with SS, it was much lower than that found in studies conducted in Japan . Differences in the prevalence of HTLV‐I‐associated diseases across countries have previously been reported; for example, the reported prevalence of uveitis is much lower in Brazil than in Japan and Martinique . Geographic location can therefore play a role in the development of certain manifestations.…”
Section: Discussioncontrasting
confidence: 83%
“…Interestingly, HAU was not diagnosed in this study, even in patients with high PVL, corroborating other studies performed in Brazil that found a lower prevalence of HAU, compared to Japanese studies. 10,11,41,42 It is possible that genetic background could play a role in the difference HAU prevalences.…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-1 is known to be transmitted by infected lymphocytes in sperm and this may contribute to the higher prevalence of the disease in women than in men (Yoshimura et al, 1993; Takahashi et al, 2000; Miyanaga et al, 2009). As for the prevalence of HU in different parts of the world, the prevalences of HU in Martinique (Merle et al, 2002) and Brazil (Rathsam-Pinheiro et al, 2009) are lower than that in Japan (Yamamoto et al, 1999; Pinheiro et al, 2006). In general, as migration to metropolitan areas is on the rise, the number of HTLV-1 carriers in metropolitan areas (for example, Tokyo) is significantly increasing (Uchimaru et al, 2008), although the number of carriers is still the highest in the endemic areas.…”
Section: Seroepidemiologymentioning
confidence: 99%